Atlas of Graft-versus-Host Disease : Approaches to Diagnosis and Treatment - Cotliar, Jonathan A. (Springer International Publishing : Imprint: Springer, 2017)
This atlas provides valuable guidance for medical students, residents, fellows, nurses, attending physicians, and other allied health professionals taking care of patients with graft-versus-host disease (GVHD). Our understanding about the intricacies of GVHD diagnosis and treatment are constantly developing as basic and translational science in the field evolves. As such, this text reflects the best current evidence we have to date for clinicians treating patients with GVHD. The Atlas of Graft-versus-Host Disease is a concise and useful graphical resource providing comprehensive guidance required for a disease entity that has a heterogeneous and complicated clinical presentation. It has been written with input of both oncologists and dermatologists, which has enabled the capture of perspectives and nuances of GVHD diagnosis and management that can influence readers with varied training backgrounds and current clinical practice, thus creating a powerful and useful resource for readers.
Keywords: Medicine.; Dermatology.; Oncology.; Pediatrics.; Surgical oncology.; elektronické knihy; electronic books